2007
DOI: 10.1213/01.ane.0000282781.56025.52
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Deliberate Hypercapnia and Hypocapnia on Intraoperative Blood Loss and Quality of Surgical Field During Functional Endoscopic Sinus Surgery

Abstract: CO2 management during functional endoscopic sinus surgery does not influence operating conditions or blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
1
40
0
1
Order By: Relevance
“…[910] Remifentanil and labetalol the two anesthetic drugs that are used in anesthesia during endoscopic sinus surgery to controlled hypotension and providing the better field of operation, but no comparative study has been performed on the use of remifentanil or labetalol for controlled hypotension during endoscopic sinus surgery. The present study was designed to assess the efficacies of labetalol and remifentanil in terms of postoperative analgesia and other complications during and after controlled hypotension for in endoscopic sinus surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[910] Remifentanil and labetalol the two anesthetic drugs that are used in anesthesia during endoscopic sinus surgery to controlled hypotension and providing the better field of operation, but no comparative study has been performed on the use of remifentanil or labetalol for controlled hypotension during endoscopic sinus surgery. The present study was designed to assess the efficacies of labetalol and remifentanil in terms of postoperative analgesia and other complications during and after controlled hypotension for in endoscopic sinus surgery.…”
Section: Discussionmentioning
confidence: 99%
“…on a scoring scale modified from Boezaart et al 17 (0: best, 10: worst) ( Table 1). 18 The extent of the surgical procedure performed was assessed using a surgical volume scale: 0 to 1 score for surgery on the maxillary and sphenoid sinuses and 0 to 2 score for ethmoid, frontal sinuses and dissection of bulky polypoid disease from the nasal cavity, yielding the maximum score of 8 per side (maximum total score of 16). 18 Increased score was given for the surgical dissection of the ethmoid, frontal sinuses and nasal polypoid disease because of frequently encountered higher blood loss in these regions.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…However, a recent study demonstrated no significant difference in the surgical conditions or blood loss among hypocapnia (end tidal carbon dioxide (ETCO 2 )  27 ± 2 mm Hg), normocapnia (ETCO 2   37 ± 2 mm Hg), or hypercapnia (ETCO 2   60 ± 2 mm Hg) in patients under propofol plus remifentanil anesthesia when heart rate and blood pressure were controlled [18]. Although this study showed that hypercapnia does not yield significantly different intraoperative bleeding, it is known that high hypercapnia produces vasodilatation, increasing cerebral blood flow and brain fullness.…”
Section: Anesthesia Considerationsmentioning
confidence: 99%